Heirs Responsibility for Damaged Notary Protocols in Indonesia: Tanggung Jawab Ahli Waris atas Dokumen Notaris yang Rusak di Indonesia - Azriel Al Rasyid; Noor Fatimah Mediawati (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Notary protocols constitute official legal archives that preserve authentic records of civil transactions and agreements, forming a foundation for legal certainty and public trust in notarial services. Specific Background: When a notary dies, these protocols—classified as state archives—must be safeguarded and transferred according to statutory procedures, yet in practice they may be left in deteriorated conditions that complicate administrative handling. Knowledge Gap: Limited clarity persists regarding the legal duties of heirs in managing, reporting, and transferring damaged protocols, particularly when archives have been destroyed by environmental factors or other uncontrollable events. Aims: This study examines the obligations of heirs concerning damaged notary protocols and analyzes the associated legal consequences using a normative-empirical legal approach supported by statutory review and interviews with the Regional Supervisory Council. Results: Findings indicate that heirs are required to report the existence of protocols within a prescribed period, coordinate with supervisory authorities, and facilitate transfer to an appointed notary; failure to do so may lead authorities to assume control to prevent legal uncertainty and protect parties who relied on the original deeds. Novelty: The study integrates doctrinal legal analysis with field evidence to clarify procedural responsibilities of heirs in post-mortem protocol management. Implications: Strengthening compliance with reporting and transfer procedures is essential to safeguard clients’ rights, maintain archival integrity, and preserve public confidence in the notarial institution. Highlights: Heirs must promptly notify supervisory authorities and arrange document transfer after the notary’s death. Authorities may intervene and appoint a custodian when families fail to act within statutory time limits. Proper handling of archives is necessary to protect parties connected to authentic deeds and avoid disputes. Keywords: Notary Protocol; Heirs Responsibility; Legal Certainty; Notarial Archives; Indonesia